Ethical Decision-Making in Healthcare: The Combined Role of Nurses and Physicians - Kateb, Areej Yousef; ALSahli, Fahad Atallah; ALHARBI, Turki Abid; Albarnawi, Rehab Taher; Alluqmani, Abrar Obeid (Journal of Posthumanism, 2024)
Ethical decision-making is essential in healthcare, necessitating a collaborative approach to navigate complex moral dilemmas. This paper analyzes the roles of nurses and physicians, establishing foundational principles of biomedical ethics: autonomy, beneficence, non-maleficence, and justice. It contrasts the medical focus on "cure" with nursing's "care," illustrating how this divergence can foster a holistic ethical framework. Nurses advocate for patients’ experiences, while physicians manage diagnosis and treatment. The report highlights the benefits of interprofessional collaboration, including improved patient safety and satisfaction, while addressing barriers like power hierarchies and communication failures. It proposes strategies for a cohesive ethical environment through interprofessional education and ethics committees, asserting that collaboration in ethical deliberation is crucial for patient safety and healthcare equity.